1994
DOI: 10.1002/ar.1092380314
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TGFβ1/β3 during early chick embryo development

Abstract: We have used an antibody against a TGF beta peptide fragment to localize this growth factor in the early chick embryo from laying to the ten-somite stage of development. Western blotting showed that the antibody reacted with both mammalian TGF beta 1 and chicken TGF beta 3. By immunocytochemistry we find that at the earliest developmental stage (stage X of Eyal-Giladi and Kochav) immunoreactivity to this antibody is primarily located in the cells of the area opaca and marginal zone, as well as in the most peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
5
0
2
Order By: Relevance
“…The ability of activin to instructively induce cardiac myogenesis in epiblast, but not in mesoderm derived from epiblast, mimics the activity of pregastrula hypoblast (Yatskievych et al, 1997) and is consistent with the localization of activin ␤ mRNAs to the chick pregastrula hypoblast (Mitrani et al, 1990). TGF␤ proteins have been detected in scattered cells of the hypoblast and in marginal zone cells of the pregastrula chick embryo (Sanders et al, 1994), and TGF␤-1 can likewise substitute for the hypoblast to induce cardiac myogenesis in epiblast. Activin and TGF␤ also have similar mesoderm-inducing activities in amphibian assays (Rosa et al, 1988;Green et al, 1992;Logan and Mohun, 1993) and act through common intracellular transducers, the Mad proteins.…”
Section: Activin/tgf␤ Signaling Acts Upstream Of Bmp Signaling In Thementioning
confidence: 71%
See 2 more Smart Citations
“…The ability of activin to instructively induce cardiac myogenesis in epiblast, but not in mesoderm derived from epiblast, mimics the activity of pregastrula hypoblast (Yatskievych et al, 1997) and is consistent with the localization of activin ␤ mRNAs to the chick pregastrula hypoblast (Mitrani et al, 1990). TGF␤ proteins have been detected in scattered cells of the hypoblast and in marginal zone cells of the pregastrula chick embryo (Sanders et al, 1994), and TGF␤-1 can likewise substitute for the hypoblast to induce cardiac myogenesis in epiblast. Activin and TGF␤ also have similar mesoderm-inducing activities in amphibian assays (Rosa et al, 1988;Green et al, 1992;Logan and Mohun, 1993) and act through common intracellular transducers, the Mad proteins.…”
Section: Activin/tgf␤ Signaling Acts Upstream Of Bmp Signaling In Thementioning
confidence: 71%
“…TGF␤ proteins can induce dorsal mesoderm from Xenopus animal caps (Rosa et al, 1988). Since TGF␤ proteins are present within some cells of the pregastrula hypoblast (Sanders et al, 1994), the ability of TGF␤-1 to substitute for hypoblast to induce cardiac myogenesis within chick posterior epiblast was also tested. Like activin, TGF␤-1 induced the appearance of cardiac myocytes in responsive epiblast in a dose-dependent manner (Fig.…”
Section: Activin/tgf␤ and Bmp-2/bmp-4 Have Distinct Cardiogenic-inducmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few reports dealing with the spatiotemporal expression of TGFβs during chick embryogenesis have been published despite the large number of morphogenetic and experimental investigations of avian embryogenesis (Boyer et al, 1999b; Choy et al, 1991; Jakowlew et al, 1994; Potts et al, 1992; Sanders et al, 1994; Yamagishi et al, 1999b). During chick cardiogenesis, TGFβ3 mRNA is expressed in the primitive heart tube at stage 8–9 (just before spontaneous beating begins).…”
Section: Tgfβ Expression During Endocardial Cushion Formationmentioning
confidence: 99%
“…TGFβ3-null mice show defective morphogenesis of palate and lung (Kaartinen et al 1995;Proetzel et al 1995). Only a few reports dealing with the spatiotemporal expression of TGFβs during chicken embryogenesis have been published, despite the large number of morphogenetic and experimental investigations of avian embryogenesis (Choy et al 1991;Potts et al 1991Potts et al , 1992Jakowlew et al 1994;Sanders et al 1994). We and others have reported that TGFβ3 plays a critical role in the formation of chick endocardial cushion tissue (Potts et al 1992;Nakajima et al 1998).…”
Section: Introductionmentioning
confidence: 99%